The complete mitogenome of Fusarium gerlachii - Kulik, Tomasz; Brankovics, Balazs; Sawicki, Jakub; van Diepeningen, Anne D (Mitochondrial DNA. Part A, DNA mapping, sequencing, and analysis, 2016)
The structure of the Fusarium gerlachii mitogenome is similar to that of closely related Fusarium graminearum; it has a total length of 93,428 bp, the base composition of the genome is: A (35.3%), T (32.8%), C (14.7%) and G (17.2%). The mitogenome contains 13 protein-coding genes, 2 ribosomal RNA (rRNA) and 28 transfer RNA (tRNA) genes. The tRNA genes range in size from 62 bp to 88 bp. The gene order is identical to that of the other Fusarium mitogenomes.
Keywords: zastoupení bazí; RNA, Transfer; Molecular Sequence Annotation; mitogenome; Fusarium; párování bází; Base Pairing; fungi; genom fungální; Genome, Fungal; anotace sekvence; F. gerlachii; DNA, Mitochondrial; Genome, Mitochondrial; genom mitochondriální; mitochondriální DNA; RNA transferová; Base Composition